1990
DOI: 10.1111/j.1365-2621.1990.tb06007.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Composition and Hydration Characteristics of Lung Protein Isolates Defatted by Several Solvents

Abstract: Different portions of a protein isolate from bovine lungs were exhaustively defatted by solvents of varying polarities. Phospholipids, cholesterol and cholesterol esters, free fatty acids, mono‐, di‐ and triacylglycerols were quantitatively determined in the extracts. Their amount was dependant on the polarity of the solvent employed. Neutral lipids were quantitatively removed by all solvents whereas the amount of phospholipids extracted increased with solvent polarity. The water monolayer capacity of the defa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The phospholipids were analysed, and phosphatidylcholine and sphingomyelin were found to be major components ( Table 1). The lipids in the isolates were similar to those reported in lung tissues (Baxter et al, 1969;Rooney et al, 1974;Ryan et al, 1980;Alcocer & Ar6as, 1990).…”
Section: Resultssupporting
confidence: 84%
“…The phospholipids were analysed, and phosphatidylcholine and sphingomyelin were found to be major components ( Table 1). The lipids in the isolates were similar to those reported in lung tissues (Baxter et al, 1969;Rooney et al, 1974;Ryan et al, 1980;Alcocer & Ar6as, 1990).…”
Section: Resultssupporting
confidence: 84%
“…Mitchell and Areas (15) suggested that the presence of insoluble protein aggregates negatively affects flow behavior. However, Alcocer and Areas (16) found that increasing flour lipid content resulted in decreased protein aggregation, resulting in less energy input in comparison to low lipid-containing flours. Indeed, higher residual oil samples (71/13/1, 55/13/1, 40/12/1, and 70/11/1) had significantly lower torque and pressure compared with other partially defatted soy flours.…”
Section: Figmentioning
confidence: 96%